2022
DOI: 10.26710/jafee.v8i1.2205
|View full text |Cite
|
Sign up to set email alerts
|

Changing Oil Prices, Exchange Rates and its Impact on Inflation in Pakistan

Abstract: Purpose: The key objective of the analysis is to explore the impact of oil prices and exchange rates on the inflation rate in Pakistan by using annual time-series data from the period 1980 to 2020. Design/Methodology/Approach: The augmented Dickey-Fuller test, bound test approach, and ARDL model are applied to achieve the objectives of the study. Findings: It is found that the crude oil prices and real effective exchange rate are found to be significant factors that influence the inflation rate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Initially its impact is very little but after 6 periods, it tends to be increasing. This finding is also an accordance with the findings of Tolasa et al (2022), Hussain et al (2022), Ellahi (2017), and Nisar and Tufail (2013). As claimed by Lim and Papi (1997), the excessive money supply is the primary source of inflation (also see, Ujkani & Gara, 2023).…”
Section: Impulse Responsesupporting
confidence: 92%
See 1 more Smart Citation
“…Initially its impact is very little but after 6 periods, it tends to be increasing. This finding is also an accordance with the findings of Tolasa et al (2022), Hussain et al (2022), Ellahi (2017), and Nisar and Tufail (2013). As claimed by Lim and Papi (1997), the excessive money supply is the primary source of inflation (also see, Ujkani & Gara, 2023).…”
Section: Impulse Responsesupporting
confidence: 92%
“…However, supply side factors that usually caused inflation includes high imports, huge external debts and government revenues (see also, (Iqbal et al, 2022;Ahmed et al, 2014a;Arif & Ali, 2012;Abdus & Zafar, 2005). The crude oil prices and the faster devaluation of the local currency also determine inflation and there is a negative correlation found between them (GENÇ et al, 2023;Hussain et al, 2022;Saleem et al, 2022). Moreover, the recent flood in the country that washed away a larger portion of crops, faster depreciation of local currency and rising of imports compared to the exports are also considered some of the important factor in creating inflation in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [17] found that exchange rate fluctuations and changes in oil prices are vital factors influencing Pakistan's inflation rate. After the pandemic and increased tension between Russia and Ukraine, more supply-side issues are arising related to oil prices that can directly or indirectly influence the prices of different sectors in oil-importing countries [18].…”
Section: Statement Of Problemmentioning
confidence: 99%